Difference between revisions of "Math 22 Lagrange Multipliers"

From Math Wiki
Jump to navigation Jump to search
 
(One intermediate revision by the same user not shown)
Line 28: Line 28:
 
!Solution:  
 
!Solution:  
 
|-
 
|-
|<math>\frac{\partial z}{\partial x}=2xy^3</math>
+
|So, <math>F(x,y,\lambda)=f(x,y)-\lambda g(x,y)=xy-\lambda (x+3y-6)=xy-\lambda x -3\lambda y+6\lambda</math>
 
|-
 
|-
|<math>\frac{\partial z}{\partial y}=3x^2y^2</math>
+
|<math>F_x(x,y,\lambda)=y-\lambda</math>
 +
|-
 +
|<math>F_y(x,y,\lambda)=x-3\lambda</math>
 +
|-
 +
|<math>F_{\lambda}(x,y,\lambda)=-x-3y+6</math>  
 
|}
 
|}
  

Latest revision as of 08:57, 18 August 2020

Method of Lagrange Multipliers

 If  has a maximum or minimum subject to the constraint , then it will occur at one of the critical numbers of the function  defined by
 .
 
 In this section, we need to set up the system of equations:
 
 
 
 

Example: Set up the Lagrange Multipliers:

1) Maximum: and Constraint

Solution:  
So,

2) Maximum: and Constraint

Solution:  
So,


Return to Topics Page

This page were made by Tri Phan